2019
DOI: 10.1136/bjsports-2018-100232
|View full text |Cite
|
Sign up to set email alerts
|

Head Injury in Soccer: From Science to the Field; summary of the head injury summit held in April 2017 in New York City, New York

Abstract: There has been an increased focus and awareness of head injury and sport-related concussion (SRC) across all sports from the medical and scientific communities, sports organisations, legislators, the media and the general population. Soccer, in particular, has been a focus of attention due to the popularity of the game, the frequency of SRC and the hypothesised effects of repetitive heading of the ball. Major League Soccer, US Soccer and the National Women’s Soccer League jointly hosted a conference entitled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 137 publications
3
56
0
Order By: Relevance
“…1,11,50,51 Therefore, it raises the question if long-distance shots that fly at higher velocities than short-distance shots, could lead to greater contact force on the head. 5,14 Results from a biomechanical study found that goal kicks and punts, which are usually long-distance shots, resulted in higher linear and rotational head accelerations. 52 Most headers for the total cohort occurred after short-distance shots of less than 5 m and only few were the result of shots from over 20 m. Additionally, the location of contacts on the players' heads is important because temporal, occipital, or parietal contact on the head may be a sign of unwanted and/or unaware contact with the ball.…”
Section: Head Injuries In Match Play and Training Sessionsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,11,50,51 Therefore, it raises the question if long-distance shots that fly at higher velocities than short-distance shots, could lead to greater contact force on the head. 5,14 Results from a biomechanical study found that goal kicks and punts, which are usually long-distance shots, resulted in higher linear and rotational head accelerations. 52 Most headers for the total cohort occurred after short-distance shots of less than 5 m and only few were the result of shots from over 20 m. Additionally, the location of contacts on the players' heads is important because temporal, occipital, or parietal contact on the head may be a sign of unwanted and/or unaware contact with the ball.…”
Section: Head Injuries In Match Play and Training Sessionsmentioning
confidence: 99%
“…3,4,6,8 The consensus statement of the head injury summit described that acute or chronic neurocognitive effects from heading are elusive, also due to different research methodologies. 5 Other research on retired football players and heading may suggest that changes are reversible or that heading may not be as harmful as commonly thought. 2 Regarding youth soccer, a review on heading in adolescent and children as a potentially dangerous play concluded that there is no evidence that heading in youth soccer causes any permanent brain injury and there is limited evidence that heading may cause concussion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is an extensive ongoing debate in the media as well as in the scientific literature on the potential negative effect of contact and collision sport participation on long-term neurocognitive function (Casson & Viano, 2019;Manley et al, 2017;Putukian et al, 2019). Specifically, it was suggested that the inherent exposure to (repeated) concussions or subconcussive blows may lead to an increased risk or earlier onset of neurodegenerative diseases and psychiatric disorders (Chiò, Benzi, Dossena, Mutani, & Mora, 2005;Kerr, Marshall, Harding, & Guskiewicz, 2012;Lehman, Hein, Baron, & Gersic, 2012;Mackay et al, 2019), declines in neurocognitive performance (Hume et al, 2017;Pearce, Rist, Fraser, Cohen, & Maller, 2018), and neuroimaging abnormalities (Koerte et al, 2016;Strain et al, 2015) in retired athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The results regarding the long-term effect of repeated subconcussive head impacts (RSHI) as experienced when heading the ball in soccer are similarly inconsistent (Putukian et al, 2019). It has been suggested that exposure to RSHI in soccer may lead to neuronal damage comparable to that of repetitive concussions (Maher, Hutchison, Cusimano, Comper, & Schweizer, 2014).…”
Section: Introductionmentioning
confidence: 99%